Predictors of outcome after total talectomy: a retrospective case series. Issue 1 (January 2021) - Hosseinzadeh, Pooya; James, Loren; Stirton, Jacob; Hamilton, Hunter; Minaie, Arya; Muchow, Ryan D.; Iwinsky, Henry J.; Talwalkar, Vishwas R.; Walker, Janet L.; Milbrandt, Todd A.
Abstract : Background: Talectomy has been used as a salvage procedure to correct severe and rigid foot deformities in patients with underlying neuromuscular conditions. Previous clinical reports have failed to compare outcomes based on the underlying condition. We report predictors of outcomes in patients who were treated with talectomy over 23 yr. Methods: We retrospectively reviewed the patients who underwent total talectomy from 1987 to 2010. Clinical results were graded as "good" and "poor" depending on postoperative pain, degree of equinus, skin findings, and the ability to brace. Postoperative lateral radiographs of the ankle were reviewed to determine tibiocalcaneal angle and retained talus. Statistical analysis was used to evaluate the effect of underlying diagnosis and tibiocalcaneal angle on the clinical outcome. Results: Thirty-eight patients (58 feet) were included in the study. The average length of follow-up was 5.1 yr. Fifty operated feet (86.2%) had a "good" outcome. Average tibiocalcaneal angle was 73.92 degrees in patients with outcomes categorized as good compared to 99.75 degrees in patients with outcomes categorized as poor ( P =0.012). Of the feet with myelomeningocele, 96.3% (26 feet) had outcomes categorized as good compared to 75% of feet (9 of 12) with arthrogryposis. The clinical outcome was significantly better in patients with myelomeningocele compared to patients with arthrogryposis ( P =0.04). Conclusions: Talectomy can be used as a salvage procedure to achieve a pain-free, plantigrade, and braceable foot in patients with a variety of musculoskeletal disorders. A tibiocalcaneal angle of less than 90 degrees at final follow-up and a diagnosis of myelomeningocele correlated with "good" clinical outcomes, aiding clinicians in preoperative stratification based on underlying diagnosis. Level of Evidence: Level III.